Project-Based Learning in EFL Classroom: Strategies for Success - Fitri Wijayanti; Avilanofa Bagus Budi (Journal of English in Academic and Professional Communication, 2023)
Project-Based Learning (PBL) is an innovative and student-centric approach to education that has gained widespread attention for its ability to engage learners in authentic and real-world problem-solving experiences. However, deploying this activity in ELT classroom is not an easy thing to do. To address this gap, this article presents detailed activities to be deployed in class, together with its fundamental principles, benefits, for teachers and students. The implementation of PBL activities in Junior High School level showcase the students’ empowerment to become active, engaged, and lifelong seekers of knowledge. The activities also align with modern workforce demands, as it equips students with 21st-century skills like adaptability, collaboration, problem-solving, and communication.